Preoperative Albumin-to-Alkaline Phosphatase Ratio as an Independent Predictor of Lymph Node Involvement in Penile Cancer - Antonio Tufano; Luigi Napolitano; Biagio Barone; Gabriele Pezone; Pierluigi Alvino; Simone Cilio; Carlo Buonerba; Giuseppina Canciello; Francesco Passaro; Sisto Perdonà (Medicina, 2024)
Background and Objectives: To investigate the role of preoperative albumin-to-alkaline phosphatase ratio (AAPR) in predicting pathologic node-positive (pN+) disease in penile cancer (PC) patients undergoing inguinal lymph node dissection (ILND). Materials and Methods: Clinical data of patients with squamous cell carcinoma (SCC) PC + ILND at a single high-volume institution between 2016 and 2021 were collected and retrospectively analyzed. An AAPR was obtained from preoperative blood analyses performed within 30 days from their scheduled surgery. A ROC curve analysis was used to assess AAPR cutoff, in addition to the Youden Index. Logistic regression analysis was utilized for an odds ratio (OR), 95% confidence interval (CI) calculations, and an estimate of pN+ disease. A p value < 0.05 was considered to be as statistically significant. Results: Overall, 42 PC patients were included in the study, with a mean age of 63.6 ± 12.9 years. The AAPR cut-off point value was determined to be 0.53. The ROC curve analysis reported an AUC of 0.698. On multivariable logistic regression analysis lymphovascular invasion (OR = 5.38; 95% CI: 1.47–9.93, p = 0.022), clinical node-positive disease (OR = 13.68; 95% CI: 4.37–43.90, p < 0.009), and albumin-to-alkaline phosphatase ratio ≤ 0.53 (OR = 3.61; 95% CI: 1.23–12.71, p = 0.032) were predictors of pN+ involvement. Conclusions: Preoperative AAPR may be a potentially valuable prognostic marker of pN+ disease in patients who underwent surgery for PC.